Politics in Organizations : Theory and Research Considerations. - Ferris, Gerald R. R. (Organizational frontiers series., 2012)
This edited volume in the SIOP Frontiers series is one of the first to look at the psychological factors behind politics and power in organizations. Noted contributors from schools of management, psychology, sociology and political science look at the theory, research, methodology and ethical issues related to organizational politics and climates. The book is divided into three parts: Part 1 looks at the historical evolution of the field; Part 2 integrates organizational politics with important organizational behavior constructs and/or areas of inquiry, for example in the chapter by Lisa Le.